Microbial consortia for bioremediation of agricultural pollutants - Ahmed, Afrina Ara; Hoque, Hifjul (Indian Farming, 2018)
Bioremediation is a natural process which involves in complete destruction of pollutants and can be achieved without using any harmful chemicals. The choice of the bioremediation strategy should be made on the basis of type of pesticide, environmental matrix and the organisms present in the ecosystem. Since the organism is the only eligible factor, the knowledge about features, advantages or disadvantages of organisms could be a decisive factor on bioremediation proficiency. To get all the benefits from this strategy it is necessary to carefully select the most adequate microorganism and the enzyme, and to have it well-characterized.